A Linear Regression Application of Comprehensive Knowledge with Attitudes Towards HIV / AIDS Sufferers in Indonesia Based on 2018 Riskesdas Data - Endang Yuswatiningsih; Agustina Maunaturrohmah (LPPM Universitas Duta Bangsa Surakarta, 2019)
Public understanding of early detection of HIV disease that is lacking should be a major concern because this will trigger the emergence of infectious disease transmission will be wider. The purpose of this study is to model comprehensive knowledge with attitudes towards HIV / AIDS sufferers in Indonesia. This type of research in this study is quantitative using secondary data from Riskesdas 2018. The method in this study uses linear regression is useful for modeling the relationship between knowledge and attitudes towards people with HIV / AIDS. The linear regression assumption is that the error follows the normal distribution, there is no problem with heteroscedasticity, and there is no autocorrelation problem. After the assumptions are met overall testing and partial testing are done. Assumption test results for normally distributed errors are met based on the Kolmogorov Smirnov test with a significance value of .400. Assumption test there is no problem with heteroscedasticity fulfilled based on the results of scatterplot that is not forming a certain pattern and is confirmed using the Spearman rho's test with a significance value of 0.245. The assumption test that there is no autocorrelation problem is also fulfilled based on the Run test with a significance value of 0.117. The results of testing the whole model using the F Test obtained fit model with a significance value of 0.001. The results of individual testing (partial) using the t-test found that knowledge has a significant influence on the attitudes of people with HIV / AIDS with a significance value of 0.001. The conclusion from this study obtained a linear regression model that is formed is attitude = -219,804 + 4,555 * knowledge means that attitude will increase by 4,555 each increase in knowledge by 1 unit.